2003
DOI: 10.1080/110241598750004788
|View full text |Cite
|
Sign up to set email alerts
|

Is pyloric function preserved in pylorus-preserving pancreaticoduodenectomy?

Abstract: After PPPD, most patients have abnormal pyloric function, but it is clinically evident in only a small proportion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…After the Imanaga reconstruction has been accomplished, a closed-type drain is placed adjacent to the pancreaticojejunostomy through the rear of the choledochojejunostomy Several authors have documented biliogastric reflux in the late postoperative period after PPPD-Traverso or PPPD with Roux-en-Y reconstruction, which restores the alimentary tract with a blind jejunal loop. 7,33,38,39 In these series, biliogastric reflux was observed in approximately half of the patients. In contrast to these results, biliogastric reflux was not observed in 13 PPPD-Imanaga patients who underwent scintigraphy more than 2 months after the PPPD-Imanaga.…”
Section: Gastrointestinal Function After Pppdmentioning
confidence: 79%
See 1 more Smart Citation
“…After the Imanaga reconstruction has been accomplished, a closed-type drain is placed adjacent to the pancreaticojejunostomy through the rear of the choledochojejunostomy Several authors have documented biliogastric reflux in the late postoperative period after PPPD-Traverso or PPPD with Roux-en-Y reconstruction, which restores the alimentary tract with a blind jejunal loop. 7,33,38,39 In these series, biliogastric reflux was observed in approximately half of the patients. In contrast to these results, biliogastric reflux was not observed in 13 PPPD-Imanaga patients who underwent scintigraphy more than 2 months after the PPPD-Imanaga.…”
Section: Gastrointestinal Function After Pppdmentioning
confidence: 79%
“…Several authors have documented biliogastric reflux in the late postoperative period after PPPD‐Traverso or PPPD with Roux‐en‐Y reconstruction, which restores the alimentary tract with a blind jejunal loop 7,33,38,39. In these series, biliogastric reflux was observed in approximately half of the patients.…”
Section: Gastrointestinal Function After Pppdmentioning
confidence: 97%
“…According to recently published reports, the reoperation rate for patients experiencing DGE as a postoperative complication is extremely low [33, [96][97][98]. Gastric emptying recovers gradually during a period of weeks to months, and only a minority of cases sustain prolonged clinical symptoms postoperatively [7,35,67,99,100]. This is in accordance with the results from studies where quality of life was evaluated after PD and superior outcomes were demonstrated for PPPD [101][102][103].…”
Section: Discussionmentioning
confidence: 95%
“…Delayed recovery of gastric motility may occur due to the decreased gastric mucosal blood flow induced by the alkaline exposure. Although the pylorus is preserved in PPPD, alkaline reflux occurs in over 70% of patients, as demonstrated by 24‐h pH monitoring . Fukuhara et al, using 24‐h bilirubin monitoring, reported that Roux‐en‐Y gastrojejunostomy after distal gastrectomy caused less bile reflux than Billroth‐I or Billroth‐II reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Although the pylorus is preserved in PPPD, alkaline reflux occurs in over 70% of patients, as demonstrated by 24-h pH monitoring. 39 Fukuhara et al, 40 using 24-h bilirubin monitoring, reported that Roux-en-Y gastrojejunostomy after distal gastrectomy caused less bile reflux than Billroth-I or Billroth-II reconstruction. This may have been the reason, for the earlier first appearance of gastric phase III after PPPD in the Roux-en-Y group than in the Traverso group.…”
Section: Discussionmentioning
confidence: 99%